Update on preclinical models of cancer therapy-related cardiac dysfunction: Challenges and perspectives. A scientific statement of the Heart Failure Association (HFA) of the ESC, the ESC Council of Cardio-Oncology, and the ESC Working Group on Cellular Biology of the Heart - Ghigo, Alessandra; Ameri, Pietro; Asnani, Aarti; Bertero, Edoardo; de Boer, Rudolf A.; Farmakis, Dimitrios; González, Arantxa; Heymans, Stephane; Ibáñez, Borja; López-Fernández, Teresa; Lyon, Alexander R.; Pollesello, Piero; et al. (European journal of heart failure, 2025)
New anticancer therapies with potential cardiovascular side effects are continuously being introduced into clinical practice, with new and often unexpected toxicities becoming apparent only after clinical introduction. These unknown toxicities should be identified and understood beforehand to better prepare patients and physicians, enabling the implementation of effective treatments. Therefore, there is a crucial need for appropriate preclinical models to understand the biological basis of their cardiotoxicity. This scientific statement summarizes the preclinical models hitherto used, from in vitro two- and three-dimensional human systems to small and large animals, to pinpoint the molecular mechanisms behind the cardiotoxicity of new-generation anticancer therapies, particularly immunotherapies, and to develop potential cardioprotective strategies. Furthermore, it discusses how preclinical models have contributed to the provocative concept of heart failure being potentially tumorigenic and how the discovery of drugs with both anticancer and cardioprotective actions has revealed a common mechanistic basis for heart failure and cancer. Finally, it discusses the existing gaps between preclinical models and clinical observations in patients, how these discrepancies affect regulatory pathways and the drug development process in cardio-oncology and provides recommendations for closing these gaps.